PENGARUH PEMBELAJARAN BERBASIS PROYEK TERHADAP PENGEMBANGAN KREATIVITAS SISWA DI SMP NEGERI 4 KOTA BENGKULU - Efendi, Sutrian; Purnama Dewi, Anniza; Wennya Naurahlatifa, Nadiahhanun; Atun Soleha, Asri; Ratnasari, Desi (Jurnal Ilmu Pendidikan Islam, 2025)
This research aims to analyze the influence of project-based learning on the development of student creativity at SMP Negeri 4 Bengkulu City. The research method used is a quantitative method with a quasi-experimental design. The population of this study was class VIII students, with a sample of 60 students divided into experimental groups and control groups. Data collection techniques are carried out through observation, questionnaires and creativity tests. The research results showed that there were significant differences in the development of creativity between the experimental group which used project-based learning and the control group which used conventional methods. The average creativity score of students in the experimental group increased by 23% compared to the control group. Thus, project-based learning can be an effective method for increasing student creativity.